Seamless integration of textile-electronics in knitted fabrics for personalized health - Hafid, Abdelakram; Gunnarsson, Emanuel; Rödby, Kristian; Seoane, Fernando (Wydawnictwo Politechniki Łódzkiej, 2022)
Development in the field of wearable technology is beginning to spread in society. It mainly refers to incorporated electronics devices which can be worn comfortably on the body. This paper presents an evaluation of a developed implementation of a well-known knitting technique to create textile-electronic interconnections that can be used for all kinds of electrical signals. Conductive textile wires have been produced and electrically characterised for power transmission, analogue, digital and biopotential signals. The results obtained for the different signal measurements are satisfactory and structures like the samples can be used for wearable applications. The results are encouraging for future development of a complete wearable garment with integration of only a minimum of necessary electronic components for supporting developers in research on for instance p-health application.
Keywords: textile-electronics; textile knitting; intarsia; wearable sensing solutions; electrical characterisation; biomedical application; elektronika tekstylna; dziewiarstwo tekstylne; intarsja; czujniki do noszenia; charakterystyka elektryczna; zastosowania biomedyczne